Ekpyrotic Nongaussianity: A Review - Jean-Luc Lehners (Advances in Astronomy)
Ekpyrotic models and their cyclic extensions solve the standard cosmological flatness, horizon, and homogeneity puzzles by postulating a slowly contracting phase of the universe prior to the big bang. This ekpyrotic phase also manages to produce a nearly scale-invariant spectrum of scalar density fluctuations but, crucially, with significant nongaussian corrections. In fact, some versions of ekpyrosis are on the borderline of being ruled out by observations, while, interestingly, the best-motivated models predict levels of nongaussianity that will be measurable by near-future experiments. Here, we review these predictions in detail, and comment on their implications.